2002
DOI: 10.1016/s0886-3350(01)01279-2
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotorsion: A possible cause of residual astigmatism in refractive surgery

Abstract: Significant cyclotorsion may occur under monocular viewing conditions. If monocular photorefractive keratectomy procedures are based on binocular keratometry readings, an undercorrection of myopic astigmatism may result. Individuals at risk should be identified before refractive keratectomy is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 10 publications
1
62
0
6
Order By: Relevance
“…Cyclotorsion can be due to many causes: i) positional (the eyes cyclorotate when the patient assumes a supine position), ii) secondary to head tilt (thus assuring a correct position on the laser bed is crucial), iii) unmasking of a cyclophoria (patients had a motility assessment preo peratively) following monocular occlusion (6,7) , or iv) secondary to distortion of the globe by the speculum. Compensating for the induced cyclotorsion as a result of assuming a supine position leads to better results of astigmatism correction (10)(11)(12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclotorsion can be due to many causes: i) positional (the eyes cyclorotate when the patient assumes a supine position), ii) secondary to head tilt (thus assuring a correct position on the laser bed is crucial), iii) unmasking of a cyclophoria (patients had a motility assessment preo peratively) following monocular occlusion (6,7) , or iv) secondary to distortion of the globe by the speculum. Compensating for the induced cyclotorsion as a result of assuming a supine position leads to better results of astigmatism correction (10)(11)(12) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have described the effect of centration and cyclotorsion correction on postoperative cylinder and uncorrected visual acuity (UDVA) in eyes with spherocylindrical errors of refraction (1,2,6,7) . Here we report the efficacy, reliability, and reproducibility of Static Cyclotorsion Correction (SCC) measurement using the Schwind Amaris excimer laser in eyes undergoing LASIK or t-PRK refractive surgery.…”
Section: Método: Oitenta Olhos (40 Pacientes) Todos Os Olhos Foram Smentioning
confidence: 99%
“…[2][3][4] The stability of fixation on the horizontal and vertical plane significantly worsens through increased amounts of blur, 8 and during surface ablation the blurring of the fixation target can increase horizontal and vertical eye movements. To our knowledge, this is the first study that addresses the question of dynamic changes of eye torsion during a simulated surface ablation.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical importance of torsional misalignments can be understood if we consider that a 101 alignment error results in a 30% astigmatic, 50% trefoil and 65% tetrafoil undercorrection. 1 It has been previously reported that eye orientation significantly changes when moving from an upright to a supine position [2][3][4] and it has been postulated that this might cause errors in astigmatic correction. Relatively little is known about dynamic torsional eye movements, although torsional eye movements during fixation are believed to be significantly higher than orthogonal eye movements.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers demonstrate some dynamic compensatory movement to keep the image at the retina aligned to a natural orientation, whereas some suggestions have been made on significant cyclotorsion occurring under monocular viewing conditions 35 . Measuring rotation when the patient is upright 36 to when the refractive treatments are performed with the patient supine may lead to ocular cyclotorsion, resulting in mismatching of the applied versus the intended profiles 37 , 38 .…”
Section: Eye-trackingmentioning
confidence: 99%